Guilty by suspicion [videorecording (DVD)] - Winkler, Irwin; De Niro, Robert; Bening, Annette; Wendt, George; Wettig, Patricia (Warner Home Video, 1998)
Based on the McCarthy witchhunts of the 1950's, tells the story of the destruction of the career of a director. In order to revive his stalled career, he is asked to testify against friends who are suspected of being Communists.